Strain hardening and strengthening mechanism of laser melting deposition (LMD) additively manufactured FeCoCrNiAl0.5 high-entropy alloy - Zhu, Lisong; Geng, Keping; Wang, Jun; Sun, Da; Shan, Mengdie; Lu, Yao; Zhang, Xuesong; Cai, Yangchuan; Han, Jian; Jiang, Zhengyi (Elsevier, 2022)
In order to develop the high-entropy alloy (HEA) with low cost and excellent mechanical properties for structural applications, the FeCoCrNiAl0.5 HEA has been fabricated by laser melting deposition, one of the advanced additive manufacturing methods. Strain hardening behaviour has been analysed and discussed using the combination of characterisation techniques. The LMD-ed FeCoCrNiAl0.5 had a true yield strength and strain of ∼463 MPa and 2.94%. Also, the true tensile strength of the LMD-ed FeCoCrNiAl0.5 reached 876 MPa, together with the ductility of 24.97% (engineering strain). The LMD-ed FeCoCrNiAl0.5 HEA exhibited a dual-phase structure of 93% face-centred cubic (FCC) phase and 6.9% ordered B2 phase. The phase boundary between the disordered FCC and ordered B2 phases played a key role in the barrier, which can block the movement of dislocations because of the lattice distortion, very large angle, and mismatch of the lattice. Dislocation pile-up and tangle caused the dislocation density near the phase boundaries to be higher than that in other areas, meanwhile, they further prevented the movement of dislocation under stress as they generated back stress, therefore LMD-ed FeCoCrNiAl0.5 HEA had a good strain hardening behaviour with a strain hardening exponent of 0.92. This study provided an innovative insight into the development of HEAs with ordered phase by laser additive manufacturing for structural applications.
Keywords: High-entropy alloy; Laser melting deposition; Strain hardening; Phase boundary; FeCoCrNiAl0.5